Peningkatan Hasil Belajar Tematik Menggunakan Model Snowball Throwing di Kelas V SDN 17 Bonjo Alam Ampek Angkek - Annisa Fauzana; Mai Sri Lena (Universitas Negeri Padang, 2022)
The aimes of the research was to inform the increase of students’ learning outputs by implementing “Snowball Throwing” model class for grade V Students at SD N 17 Bonjo Alam Ampek Angkek. This research was a classroom action reasearch. The results showed the improvement of students’ learning output, they were : a) observation results of the lesson plan (RPP) in cycle I 86,10%, it increased in cycle II became 94,44%. b) observation on teacher’s aspects in cycle 1 : 86,10%, it increased into 94,44%. c) the result of students’ activities in cycle I : 86,10%, it increased in cylce II : 94,44%. d) Students’ learning assessment at cycle I is avaraged 77,87% with 72,27% furthermore it was increased in cycle II became 86,36%.